2020
DOI: 10.3389/fpubh.2019.00420
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Self-Stigma, Self-Esteem, and Asthma Control: A Preliminary Cross-Sectional Study Among Adult Asthmatic Patients in Selangor, Malaysia

Abstract: Purpose: The elusive goal of asthma management guidelines is to achieve and maintain good asthma control in asthmatic patients. Against a background of long-term respiratory limitations when living with asthma, stigma and low self-esteem have also been identified as the social phenomenon among adult asthmatics. This study aimed to assess the levels of self-stigma, self-esteem, and asthma control, and to investigate the impact of self-stigma and self-esteem as psychosocial factors on asthma control in Malaysian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
1
14
1
Order By: Relevance
“…Our study had also revealed that controlled asthma patients were less stigmatized compared to uncontrolled ones. This is supported by a study from Malaysia, which showed that asthma control in adult patients was negatively influenced by the reported degree of stigmatization 35 . Previous studies focused on asthma among children 5 and adults 4 found associations between correct inhaler use and level of asthma control; however, we did not find such an association in our study.…”
Section: Discussionsupporting
confidence: 65%
“…Our study had also revealed that controlled asthma patients were less stigmatized compared to uncontrolled ones. This is supported by a study from Malaysia, which showed that asthma control in adult patients was negatively influenced by the reported degree of stigmatization 35 . Previous studies focused on asthma among children 5 and adults 4 found associations between correct inhaler use and level of asthma control; however, we did not find such an association in our study.…”
Section: Discussionsupporting
confidence: 65%
“…Despite this, 75% of patients perceived their asthma to be controlled thereby highlighting the mismatch between reality and patients' attitude toward their symptoms [32]. Other independent studies carried out at tertiary care centers in Malaysia also highlight the importance of patient behavior and perception in achieving optimum asthma control [33][34][35].…”
Section: F I G U R E 1 Factors Contributing To Uncontrolled Asthmamentioning
confidence: 99%
“…In Malaysia, the Ministry of Health had taken important initiatives in 2004 to provide counselling and education to patients with chronic diseases including asthma in the form of dedicated centers called Medication Therapy Adherence Clinics (MTAC). With the overall adherence to treatment being low for chronic diseases, the objective of MTAC was to achieve an increase in treatment adherence among such patients [34,36,37]. In a survey in 2017 that included Malaysian Healthcare Professionals (HCPs), incorrect inhaler techniques followed by non-compliance to treatment remained to be the biggest contributors to uncontrolled asthma [38].…”
Section: Non-compliance To Treatmentmentioning
confidence: 99%
“…The study also found that perceived stigma was significantly associated with dyspnoea and cough symptoms. Ahmad et al [24] reported that self-stigma and self-esteem is a predictor of poor asthma control. 1 The interaction of respiratory disease, need for medication and stigma.…”
Section: Impact Of Medication-related Stigma On Health Outcomesmentioning
confidence: 99%
“…A hmad et al . [ 24 ] reported that self-stigma and self-esteem is a predictor of poor asthma control.…”
Section: Impact Of Medication-related Stigma On Health Outcomesmentioning
confidence: 99%